Vacancy encounter model for stochastically fluctuating electric field gradients in the Cu3Au crystal structure. Issue 16 (18th August 2019) - Zacate, Matthew O.; Williams, Justin D.
ABSTRACT: A class of experimental techniques known as hyperfine methods can be used to measure electric field gradients (EFGs) through the hyperfine interaction experienced by tracer nuclei. When EFGs fluctuate at rates comparable to the inverse characteristic timescale of the hyperfine method, there is a loss of signal coherence that can be used to determine EFG fluctuation rates. This has been used to measure, for example, EFG fluctuations accompanying atomic jumps of radiotracers using perturbed angular correlation spectroscopy (PAC). Nominally, there is a one-to-one correspondence between EFG fluctuation and tracer jump, but when tracer jumps are mediated by a vacancy diffusion mechanism, a subset of multiple tracer-vacancy exchanges will not affect spectra when they occur much faster than the hyperfine timescale, leading to an underestimate of underlying tracer jump rate if this correlated random-walk effect is not taken into consideration. The present work calculates the factor by which EFG fluctuation rate differs from tracer jump rate based on a time-dependent, random-walk analysis of tracer displacement probabilities in a vacancy encounter model for the special case of self-diffusion in the L 12 crystal structure.